Living Quran sebagai Wadah Baru dalam Penelitian Tafsir - Jailani; Ahmad Yusam Thobroni (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2022)
In essence, the study of the Qur'an does not always focus on the text of the Qur'an (mā fil al-Qur'an) and what happens around the Qur'an (ma haul al-Qur'an), but it is possible also extends to the living Qur'an, consisting of social phenomena regarding the existence of the Qur'an in certain Muslim communities, or the daily lives of people who interact with the Qur'an, in other words the living Qur'an in society. This library research explores data from relevant library materials as a data source and uses qualitative descriptive methods to describe the problems studied. This article aims to explain the development of Al-Qur'an research into the realm of the living Qur'an, where so far Al-Qur'an research has mostly only focused on the text. Thus, the study of the living Qur'an can be an alternative in developing contemporary Al-Qur'an studies.